Do Infant Cleft Dimensions Have an Influence on Occlusal Relations? A Subgroup Analysis Within an RCT of Primary Surgery in Patients With Unilateral Cleft Lip and Palate. (March 2020) - Botticelli, Susanna; Küseler, Annelise; Marcusson, Agneta; Mølsted, Kirsten; Nørholt, Sven E.; Cattaneo, Paolo M.; Pedersen, Thomas K.
Aim: To investigate whether infant cleft dimensions, in a surgical protocol with early or delayed hard palate closure, influence occlusion before orthodontics. Design: Subgroup analysis within a randomized trial of primary surgery (Scandcleft). Setting: Tertiary health care. One surgical centre. Patients and Methods: A total of 122 unilateral cleft lip and palate infants received primary cheilo-rhinoplasty and soft palate closure at age 4 months and were randomized for hard palate closure at age 12 versus 36 months. A novel 3D analysis of cleft size and morphology was performed on digitized presurgical models. Occlusion was scored on 8-year models using the modified Huddarth–Bodenham (MHB) Index and the Goslon Yardstick. Main Outcome Measurements: Differences in MHB and Goslon scores among the 2 surgical groups adjusted for cleft size. Results: The crude analysis showed no difference between the 2 surgical groups in Goslon scores but a better MHB ( P = .006) for the group who received delayed hard palate closure. When adjusting for the ratio between cleft surface and palatal surface (3D Infant Cleft Severity Ratio) and for posterior cleft dimensions at tuberosity level, the delayed hard palate closure group received 3.65 points better for MHB (confidence interval: 1.81; 5.48; P < .001) and showed a trend for reduced risk of receiving a Goslon of 4 or 5 ( P = .052). For posterior clefts larger than 9 mm, the Goslon score was better in the delayed hard palate closure group ( P = .033). Conclusions: Seen from an orthodontic perspective, when the soft palate is closed first, and the cleft is large, the timing of hard palate closure should be planned in relation to posterior cleft size.